Architecture of knowledge management system in mobile computing environment - Wan Mayu Othman, Wan Noor Rafida; Abdullah, Rusli; Selamat, Mohd Hasan; Jaafar, Azmi; Wan Ishak, Wan Roslina (Universiti Utara Malaysia, 2008)
Collaborative knowledge management (KM) system for organizational learning, addressing the needs of the individual within a purposeful context should be improved in term of organizational responsiveness, innovation, competency and efficiency. Mobile devices, such as Personal Digital Assistants (PDAs), evolve rapidly and addition to the capabilities of these devices, new mobile communication technologies, such as Wireless LAN, enable ‘anytime’ and ‘anywhere’ access to information infrastructures and integrate the devices as the front ends of mobile information systems. In implementing the KM system in mobile computing, there are many frameworks but lack of implementation in bioinformatics domain. Therefore, this research is an attempt to develop a framework for mobile knowledge management in bioinformatics domain especially in herbs plantation and formulate this concept in order to deliver the best information to the users, organizations in term of collaboration environment.